LeFort Fractures - Ikeda, Allison K.; Burke, Andrea B. (Seminars in Plastic Surgery, 2021)
Consultations for management of facial fractures in the emergency setting are not uncommon for the oral maxillofacial surgeon, otolaryngologist, and/or plastic surgeon. This necessitates a knowledge foundation and working understanding of the evaluation, assessment, and timely management. Here, we will focus on the workup and management of LeFort fractures.
Keywords: midface fractures; lefort fractures; dentoalveolar fractures; palatal fractures; dental trauma